Geografov pogled na tuja zemljepisna imena v Slovenskem pravopisu 2001 - Kladnik, Drago (Geografski vestnik, 2005)
This article analyzes foreign geographical names from the dictionary section of the 2001 edition of Slovene ortography as a case of study for the more general problem of their use from the standpoint of both orthographic rules and UN resolutions which have arisen as a result of the efforts the UNGEGEN association of experts. A detailed analysis has shown that there are still a number of unresolved issues among the 2000 or so foreign geographical names which are included, about three-fifths of which have been Slovenized.
Keywords: geografska imena; slovenski geografi; Slovene; slovenščina; standardizacija; Slovenski pravopis